Gene sequence variants PPARGC1Ars8192678, PPARG2rs1801282, FTORS9939609, LEPRS7799039 and LEPRRS1137101 in non-alcoholic fatty liver disease - Pankova, Ekaterina D.; Chulkov, Vasiliy S.; Gavrilova, Elena S.; Zotova, Maria A.; Sumerkina, Veronika A.; Zhmaylova, Svetlana V.; Okonenko, Tatiana I. (Saratov Medical Journal, 2023)
Objective: assessing the association of sequence variants rs8192678, rs1801282, rs9939609, rs7799039 and rs1137101in PPARGC1A, PPARG2, FTO, LEP and LEPR genes, respectively,with non-alcoholic fatty liver disease (NAFLD) inyounger adults (18-44 years old) of the Russian Federation. Materials and Methods. Our case-control study encompassed 100 patients distributed between two groups: Group 1 (cases) with patients suffering from NAFLD (n=50) andGroup 2 (controls) with individuals without it (n=50). All subjects underwent a conventional sonography of their liver and shear wave elastography (Aixplorer®, France): both ultrasound examinations assessed the severity of liver steatosis and fibrosis. Results. We discovered two sequence variants associated with an increased risk of NAFLD in women: rs9939609 and rs7799039: A/A rs9939609 genotype (OR 5.33, 95% CI 1.14-24.90,p=0.041) and G/G rs7799039genotype (OR 7.5, 95% CI 1.04- 54.12,p=0.026). Conclusion.The A/A genotype of the rs9939609 gene in younger women of the Russian population yielded the fivefold increase in the likelihood of NAFLD, whereas the G/G genotype of the rs7799039 gene resulted in a 7.5-fold likelihood ofNAFLD occurrence